1991
DOI: 10.1520/jfs13202j
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Remains by Comparison of Frontal Sinus Radiographs: A Series of Four Cases

Abstract: The value for identification purposes of the radiographic frontal sinus outline, which is unique to each individual and remains constant throughout that individual's lifetime, is discussed. A general discussion of identification using frontal sinus X-rays is presented, along with four cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 7 publications
0
31
0
3
Order By: Relevance
“…Culbert and Law performed the first radiographic comparison of paranasal sinuses in body identification although these were of the mastoid air cells and the identification was confirmed in part by the decedents dental restorations [14]. Since then others have undertaken frontal sinus identification and have found that it has been highly useful [15][16][17]. Christensen (2004) questioned the scientific validity and potential error rates of using frontal sinuses for body identification in light of the Daubert v. Merrel-Dow Pharmaceuticals decision by the United States Supreme Court [18].…”
Section: Special Use Of Radiology In Identification-frontal Sinusesmentioning
confidence: 99%
“…Culbert and Law performed the first radiographic comparison of paranasal sinuses in body identification although these were of the mastoid air cells and the identification was confirmed in part by the decedents dental restorations [14]. Since then others have undertaken frontal sinus identification and have found that it has been highly useful [15][16][17]. Christensen (2004) questioned the scientific validity and potential error rates of using frontal sinuses for body identification in light of the Daubert v. Merrel-Dow Pharmaceuticals decision by the United States Supreme Court [18].…”
Section: Special Use Of Radiology In Identification-frontal Sinusesmentioning
confidence: 99%
“…Many parts of the skeleton as thorax, vertebrae, shoulder [3], skull [4] and mastoid process [5] can be used for identification of a person. Most reliable parts of the skeleton for identification are those which are anatomically variable or which exhibit change due to trauma, illness or surgical intervention [6][7][8][9]. Frontal sinus has great variability and its structure does not change after the age of 20 years except very rare occurrences as fractures, tumors or severe infections [1,7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In 1927, Culbert and Law made the first identification of human remains by comparison of antemortem and postmortem radiographs of the frontal sinuses. The degree of human variation in sinus patterns, based on size, asymmetry, outline, partial septia, and supraorbital cells, makes effective comparison for identification possible (Christensen 2005;Kirk et al 2002;Marlin et al 1991;Nambiar et al 1999;Smith et al 2010).…”
Section: Positive Identification Of Individuals By Comparison Of Antementioning
confidence: 99%